PENGARUH LAMA PERENDAMAN DAN KONSENTRASI HORMON GA3 TERHADAP PERTUMBUHAN BENIH JATI DI PERSEMAIAN - Kurniawan, Andri (Jurnal Agroekoteknologi, 2017)
This research was aimed to know the effect of the interaction between soaking time and the concentration of GA3 hormones that affect the vigor, and viability of seeds Teak (Tectona grandis Lf) in the nursery, as well as finding the length of time of immersion and the best hormone concentration GA3 on vigor, and viability of seeds teak in the nursery. Experiments Used A Randomized Block Design as factorial, which consisted of two factors: the length of immersion and concentration of GA3 hormones. The first factor was the length of immersion (W), consisting of four levels: w1 = Immersion 6 hours in GA3, w2 = Immersion 12 hours in GA3, w3 = Immersion 18 hours in GA3 and w4 = Immersion 24 hours in GA3. The second factor was the concentration of hormones GA3 (A), consisted of four levels: a1 = concentration of 250 ppm GA3 hormones, a2 = concentration of 500 ppm GA3 hormones, a3 = concentration of 750 ppm GA3 hormones, a4 = concentration of 1000 ppm GA3 hormones. The results showed that an interaction between the length of immersion and the concentration of the hormone GA3 on plant height aged 30, 45, 75 and 90 HST. Interaction treatment of fluid concentration of GA3 hormone and the best immersion time from observation of the best observation of the best plant that was combination of concentration 750 ppm with time of soaking 24 hours.Keywords: Seeds, quality, Giberalin hormone, Variability, Vigor